PENGABDIAN DONOR DARAH PADA MASYARAKAT DI MASA PANDEMI COVID-19 - Ratna Damayanti; Siti Maryam (Adi Widya : Jurnal Pengabdian Masyarakat, 2021)
Blood is an important component of the human body, therefore the supply of blood at the Indonesian Red Cross must be maintained. In the era of the Covid-19 pandemic that hit Indonesia, the amount of blood supply at the Indonesian Red Cross decreased. Seeing this condition, lecturers and students from the Management Program of the Universitas Islam Batik Surakarta initiated blood donation activities to the community with the aim of providing education and socialization of the importance of blood donation in the pandemic era, increasing the number of blood bags, humanitarian efforts to help others and a concrete manifestation of the implementation of community service as one of the Tri Dharma of Higher Education. The activity was held on October 14, 2020 at the Keluarahan Tipes, Serengan with health protocol and 3M principles. Participants who registered were 28 participants, who qualified as donors as many as 25 participants. The amount of blood that was collected was as many as 25 bags. The result, the event can run smoothly and orderly and it is hoped that this activity can be held regularly.